2015
DOI: 10.5601/jelem.2014.19.4.812
|View full text |Cite
|
Sign up to set email alerts
|

Content of some chemical components in carrot (Daucus carota L.)  roots depending on growth stimulators and stubble crops

Abstract: Agronomic factors, and mineral fertilization in particular, have a strong impact on the quality of carrot roots. In recent years, researchers have begun to design eco-friendly agricultural practices that would stimulate the quality and yield of carrot roots. Our aim has been to analyse selected quality parameters pertaining to the chemical composition of carrot roots, and relate them to the application of different growth stimulators and cover crops. For this purpose, a field experiment was conducted in 2009-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…A study carried out in the Czech Republic showed that three times titanium foliar application in the form of Ti-citrate during potato grown on Chernozem (at the beginning of June with a plant height of 30 cm and repeated treatment in two-week intervals) in the dose of 10 g Ti*ha -1 in each treatment did not have any effect on the dry matter of mature tubers of 'Cordoba' cultivar and resulted only in a slight increase in the nitrogen and magnesium content in tubers (Tlustoš et al, 2005). In a study carried out by other authors, Tytanit ® application caused an increase in the magnesium and sodium content and a decrease in the calcium content in carrot roots (Kwiatkowski et al, 2015). Tytanit ® caused also an increase in the sodium content and a decrease in the calcium and magnesium content in celery (Kalembasa et al, 2014).…”
Section: Weather Conditions In Potato Growing Seasonmentioning
confidence: 77%
See 2 more Smart Citations
“…A study carried out in the Czech Republic showed that three times titanium foliar application in the form of Ti-citrate during potato grown on Chernozem (at the beginning of June with a plant height of 30 cm and repeated treatment in two-week intervals) in the dose of 10 g Ti*ha -1 in each treatment did not have any effect on the dry matter of mature tubers of 'Cordoba' cultivar and resulted only in a slight increase in the nitrogen and magnesium content in tubers (Tlustoš et al, 2005). In a study carried out by other authors, Tytanit ® application caused an increase in the magnesium and sodium content and a decrease in the calcium content in carrot roots (Kwiatkowski et al, 2015). Tytanit ® caused also an increase in the sodium content and a decrease in the calcium and magnesium content in celery (Kalembasa et al, 2014).…”
Section: Weather Conditions In Potato Growing Seasonmentioning
confidence: 77%
“…Following Tytanit ® application, the weight ratios of Ca:P, K:Ca and K:Mg in immature potato tubers were similar and the weight ratios of N:S, Na:Ca and Na:Mg were broader compared to the cultivation without the growth stimulant application, although the ratio of the sum of univalent cations to the sum of bivalent cations was at the same level, both in cultivations with and without Tytanit ® (Table 6). Tytanit ® application caused a narrowing of the weight ratio of Ca:Mg and K:Mg in carrot roots (Kwiatkowski et al, 2015). The molar ratios between K:Ca, K:Mg, Na:Ca and Na:Mg in celery were differentiated under the influence of Tytanit ® .…”
Section: Roots Most Macroelements Are Taken Up By a Combination Of Tmentioning
confidence: 94%
See 1 more Smart Citation
“…Following the simultaneous application of both preparations, they obtained a 37% reduction in nitrate content, while following the application of AlgaminoPlant only a 15% reduction. In the study by Kwiatkowski et al [54], the reduction of nitrate content in carrot roots (by 12-18%) after application of biostimulant (Asahi, Bio-algeen and Tytanit) has been presented.…”
Section: Nitrate Contentmentioning
confidence: 99%
“…If one od the effects of titanium is the enhancement of plant growth, a higher energy will be required, so inducing more starch degradation with a concomitant decrease of the levels in root and leaf [Carvajal and Alcaraz 1998]. Titanium foliar applications caused an increase in ascorbic acid content in pepper fruits [Martinez-Sanchez et al 1993], an increase in the ascorbic acid and total sugars contents in carrot roots and significantly reduced the nitrate content, but did not have any effect on the dry matter, carotenoid or phenolic content [Kwiatkowski et al 2013[Kwiatkowski et al , 2015. Biacs et al [1988] reported that Titavit ® (titanium ascorbate) caused an increase in vitamin C, total organic acid and sugar content in tomato fruit, whereas a study carried out by Kleiber and Markiewicz [2013] showed no significant effect of Tytanit ® on dry matter or sugars contents in tomato fruits grown in a greenhouse, or their active acidity.…”
Section: Introductionmentioning
confidence: 99%